Artifical Intelligence Librarian as Promotion of IAIN Lhokseumawe Library in the Revolutionary Era 4.0 - Hayani, Aida; Aprilia Sari, Evi; Sukiman, Sukiman (Universitas Muhammadiyah Yogyakarta, 2021)
Era 4.0. is a revolution in the industrial world, in the era referred to as the phenomenon distruptive innovation. In the industrial era 4.0, the emphasis lies on the digital economy pattern, artificial intelligence (artificial intelligence) big data, robotics, and automation. The impact of the industrial era 4.0 influential in various fields of work are no exception librarians. Librarian is someone who has the ability and expertise librarianship the librarians in charge to prepare themselves to face the era that is the way to equip themselves with information technology and analytical capabilities of the library so that airport users effective. Then by applying a librarian AI (artificial intelligence) to guide users in using the integrated library information. The presence of librarians AI (artificial intelligence) at IAIN Lhokseumawe made of evidence that has entered the era of disruption 4.0 will be the college library promotion strategy.